2007
DOI: 10.1016/j.yexcr.2006.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of clusterin expression in mammary epithelial cells

Abstract: Mammary epithelial cells undergo changes in growth, invasion, differentiation, and dedifferentiation throughout much of adult hood, and most strikingly during pregnancy, lactation, and involution. Clusterin is a multifunctional glycoprotein that is involved in the differentiation and morphogenesis of epithelia, and that is important in the regulation of postnatal mammary gland development. However, the mechanisms that regulate clusterin expression are still poorly understood. Here, we show that clusterin is up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 38 publications
2
12
1
Order By: Relevance
“…A previous study has proposed that sCLU has a cytoprotective effect, whereas elevated levels of nCLU may trigger cell death (Criswell et al 2003). Overexpression of sCLU has been demonstrated in various malignancies, such as colorectal (Chen et al 2003), prostate (Pins et al 2004), breast (Itahara et al 2007), renal (Kurahashi et al 2005) and liver cancers (Kang et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has proposed that sCLU has a cytoprotective effect, whereas elevated levels of nCLU may trigger cell death (Criswell et al 2003). Overexpression of sCLU has been demonstrated in various malignancies, such as colorectal (Chen et al 2003), prostate (Pins et al 2004), breast (Itahara et al 2007), renal (Kurahashi et al 2005) and liver cancers (Kang et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…SGP-2/clusterin has diverse functions, including lipid transport, complement inhibition, and regulation of apoptosis (47). During mouse mammary gland development, SGP-2/clusterin is upregulated twice, at the end of pregnancy and at the beginning of the involution, when dramatic phenotypic and functional changes occur in the mammary gland (24). Although SGP-2/clusterin is associated with apoptosis during involution, there is accumulating evidence suggesting that it is an antiapoptotic protein associated with both cancer drug therapy resistance and cellular protection against exogenous stresses (36,48,49).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that clusterin has a cytoprotective role against oxidants. 19 , 20 Clusterin has been reported as a multifunctional protein to prevent protein aggregation, to induce apoptosis of inflammatory cells as well as to inhibit complement. 20 , 21 In addition, clusterin as a sensor of oxidative and proteotoxic stress, it is implicated in numerous age-related diseases including neuro-degeneration, cardiovascular diseases, metabolic syndromes, inflammation, and cancer.…”
Section: Discussionmentioning
confidence: 99%